Integration of Digital Finance, Contract Farming, and Supply Chain Finance: Empirical Evidence from Smallholder Oil Palm Farmers in West Kalimantan - Denashurya, Nugra Irianta; Azizu, Muhamad Noor (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
The agricultural sector in Indonesia, particularly the oil palm industry, faces persistent challenges in improving smallholder welfare, stabilizing income, and ensuring financial inclusion. Smallholder oil palm farmers in West Kalimantan often experience limited access to formal financial services, price volatility, and cash flow instability due to weak market linkages and dependence on middlemen. This study aims to analyze the relationship between the adoption of digital financial services, contract farming arrangements, and access to supply chain financing among smallholder oil palm farmers in West Kalimantan. Using a mixed-method approach, quantitative data were obtained from 210 smallholder farmers through structured questionnaires, while qualitative insights were gathered through in-depth interviews with key stakeholders, including cooperatives, off-takers, and financial institutions. The results show that the implementation of digital financial technology (fintech) significantly increases farmers’ access to supply chain financing through improved financial literacy, transaction transparency, and digital credit scoring mechanisms. Furthermore, contract farming serves as an effective intermediary that strengthens the trust between farmers and financial institutions, thereby reducing financing risks. The integration of these three instruments, digital finance, contract farming, and supply chain finance, creates a synergistic model that supports sustainable palm oil production, enhances smallholders’ income stability, and reduces transaction inefficiencies across the value chain. This research provides new empirical evidence on the importance of integrated digital financial ecosystems in supporting the resilience and competitiveness of smallholder farmers. Policy recommendations include the need for stronger institutional collaboration, digital infrastructure development, and the establishment of inclusive financial platforms tailored to smallholder characteristics.